Learning Plant Biodiversity in Nature: The Use of the Citizen–Science Platform iNaturalist as a Collaborative Tool in Secondary Education - Echeverria, Andres; Ariz, Idoia; Moreno, Judit; Peralta, Javier; Gonzalez, Esther M. (Sustainability, 2021)
Biodiversity is a concept of great scientific interest and social value studied in different subjects of the secondary education curriculum. Citizen–science programs may contribute to increasing the engagement of students when studying biodiversity. This work aimed to explore the use of the citizen–science platform iNaturalist as a complement of the elaboration of herbaria in an outdoor activity for 4th course 16-year-old students in the Basaula Reserve. The platform iNaturalist was chosen for its suitability to develop collaborative projects in an educational context. The Basaula project was created and 122 students were trained to record plant species in an outdoor activity. A total of 32 species were recorded, among them the most abundant were beech (Fagus sylvatica) and holm oak (Quercus ilex). The students positively evaluated their experience, highlighting its adequacy to record biodiversity data and make a virtual herbarium. Students valued the innovative character of iNaturalist and its usefulness for research but also the opportunity to integrate mobile devices in school education. We concluded that iNaturalist is a valuable tool to carry out collaborative projects dealing with biodiversity in secondary education.
Keywords: biodiversity informatics; citizen–science; iNaturalist; outdoor education; secondary education; smartphone applications; species identification